New locality for the rare sigmodontine Abrawayaomys ruschii (Rodentia, Cricetidae) in Argentina, with comments about its regional conservation status - Cruz, María Paula (2019)
We document a new locality for the rare sylvan sigmodontine Abrawayaomys ruschii from Misiones, Argentina. The individual, recognized by its distinctive spiny hairs, was recovered from a scat of an ocelot, Leopardus pardalis (Mammalia, Felidae). This record contributes to f ll the gap between previous localities.